2015
DOI: 10.1007/s10548-015-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias by Gender Interaction on N170 Response to Emotional Facial Expressions in Major and Minor Depression

Abstract: States of depression are considered to relate to a cognitive bias reactivity to emotional events. Moreover, gender effect may influence differences in emotional processing. The current study is to investigate whether there is an interaction of cognitive bias by gender on emotional processing in minor depression (MiD) and major depression (MaD). N170 component was obtained during a visual emotional oddball paradigm to manipulate the processing of emotional information in 33 MiD, 36 MaD, and 32 controls (CN). Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
2
17
0
2
Order By: Relevance
“…In addition, a review (Bourke et al, 2010 ) revealed that compared with healthy individuals, patients with depression allocate more (less) attention resources to sad (pleasant) facial expressions, while processing ordinary facial expressions, but numerous studies have shown that the ACC of recognizing ordinary facial expressions showed no significant difference between these two groups, which supports the results of the present study to some extent. In terms of RT, the patients’ RT was longer than that of healthy individuals, which was consistent with the results of patients processing ordinary facial expressions (Wu et al, 2016 ; Zhang et al, 2016 ). However, Dai et al ( 2016 ) found that the RT of patients with depression and healthy individuals processing neutral expression showed no significant difference, while the patients’ RT of processing sad expression was shorter than that of healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, a review (Bourke et al, 2010 ) revealed that compared with healthy individuals, patients with depression allocate more (less) attention resources to sad (pleasant) facial expressions, while processing ordinary facial expressions, but numerous studies have shown that the ACC of recognizing ordinary facial expressions showed no significant difference between these two groups, which supports the results of the present study to some extent. In terms of RT, the patients’ RT was longer than that of healthy individuals, which was consistent with the results of patients processing ordinary facial expressions (Wu et al, 2016 ; Zhang et al, 2016 ). However, Dai et al ( 2016 ) found that the RT of patients with depression and healthy individuals processing neutral expression showed no significant difference, while the patients’ RT of processing sad expression was shorter than that of healthy individuals.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings were also compatible with previous study. Recently, an event-related potential study suggested that female depression may be more vulnerable that male during emotional face processing with the unconscious negative cognitive bias, and considered that unconscious cognitive bias may be modulated by sex effects [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The disease severity of our subjects (mean HAMD-17 score: 26.95 for active rTMS, and 25.5 for sham rTMS) were more severe than those of their study (mean HRSD-17 score: 16 for active rTMS, and 13.1 for sham rTMS). Indeed, a series of studies have shown different emotional processing between minor depression and major depression and different mechanisms of electrophysiological damage (36).…”
Section: Discussionmentioning
confidence: 99%